Do older consumers purchase differently? : the effect of age on brand awareness, consideration, and purchase : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Mecredy, Philip (Massey University, 2022)
The spending power of older consumers is rapidly rising as global populations continue to age. Yet, little is known about how ageing and its underlying mechanisms impact consumer behaviour. Without knowing whether the purchase patterns of older consumers differ from younger consumers, marketers may be unwisely neglecting or ineffectively targeting older consumers. Thus, across four studies, this thesis investigates whether, how, and why brand awareness, consideration, and purchase differ between older and younger consumers. This research finds that older and younger consumers display similar patterns of double jeopardy and brand duplication in their awareness and consideration of competing brands. Despite these similarities, an inverse-U shape is found for brand recognition and brand recall with the number of brands recognised and recalled increasing across age before slowing down and then declining. A similar inverse-U shape is found for brand consideration in subscription markets. For brand consideration and purchase sets in repertoire markets, a linear decline is initially found across age. However, when controlling for purchase rates to reflect changes in category purchasing, older consumers are aware of and consider more brands than younger consumers. Older consumers also show small increases in purchase loyalty across age groups for supermarket store choice and toothpaste, but not for fruit juice and pharmaceutical prescribing. These results provide the first conclusive evidence of age-related loyalty in some low-involvement categories, as loyalty measures used in prior studies are confounded by category purchase rates. While no loyalty differences were found across age groups for prescribing behaviour, longitudinal analysis reveals that physicians, regardless of age, become less reliant on their core armamentarium as they age and accumulate experience. Taken together, the research indicates that age-related loyalty patterns do sometimes occur, but cannot be explained by differences in awareness and consideration or the mechanisms that would affect these metrics (e.g. cognitive decline and biological ageing). Rather, the most likely explanation is that age-related effects are primarily driven by household lifecycle and accumulated experience. The findings provide strong implications on how to transition older consumers through the brand purchase funnel and outlines a blueprint for future studies of loyalty across age.
Listed in 2022 Dean's List of Exceptional Theses
Keywords: Older consumers; Brand choice; Dean's List of Exceptional Theses; 350601 Consumer behaviour